ロケット ニヨル デンシ ミツド カンソク - 宮崎, 茂; ミヤザキ, シゲル; MIYAZAKI, Shigeru (国立極地研究所, 1975)
P(論文) 昭和基地ロケット実験の電子密度分布の観測結果のうち.1971～72年にわたる2年間のデータについて概報する.この間,電子密度分布は高度70～130 kmの領域に関して,S-160JA 2機,S-210JA 8 機,計10機のデータが得られた. The twelfth and thirteenth Japanese Antarctic Research Expeditions (JARE) carried out firings of two S-160JA rockets and twelve S-210JA pockets to observe the polar ionosphere and auroral phenomena at Syowa Station (69°00' S, 39°35' E; geomagnetic lat. 69.6°S, long. 77.1°E) in Antarctica. The electron density profiles of the ionosphere obtained by the two S-160JA rockets and eight S-210JA rockets experiments are given in this preliminary report. departmental bulletin paper